2010 update of the ASAS/EULAR recommendations for the management of ankylosing spondylitis. Issue 6 (2nd May 2011) - Braun, J; van den Berg, R; Baraliakos, X; Boehm, H; Burgos-Vargas, R; Collantes-Estevez, E; Dagfinrud, H; Dijkmans, B; Dougados, M; Emery, P; Geher, P; Hammoudeh, M; et al.
Abstract : This first update of the ASAS/EULAR recommendations on the management of ankylosing spondylitis (AS) is based on the original paper, a systematic review of existing recommendations and the literature since 2005 and the discussion and agreement among 21 international experts, 2 patients and 2 physiotherapists in a meeting in February 2010. Each original bullet point was discussed in detail and reworded if necessary. Decisions on new recommendations were made — if necessary after voting. The strength of the recommendations (SOR) was scored on an 11-point numerical rating scale after the meeting by email. These recommendations apply to patients of all ages that fulfill the modified NY criteria for AS, independent of extra-articular manifestations, and they take into account all drug and non-drug interventions related to AS. Four overarching principles were introduced, implying that one bullet has been moved to this section. There are now 11 bullet points including 2 new ones, one related to extra-articular manifestations and one to changes in the disease course. With a mean score of 9.1 (range 8-10) the SOR was generally very good.